IMF technical assistance : independent evaluation office - Selowsky, Marcelo; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This evaluation examines the technical assistance provided by the International Monetary Fund to its member countries.
"Prepared by a team headed by Marcelo Selowsky"--p. viii.
Includes bibliographical references: p. 75-78.
osc 05/08/2016
Loans
Keywords: International Monetary Fund - evaluation; Technical assistance - evaluation